How catalysts affect the growth of single-walled carbon nanotubes on substrates - Li, Yan (Advanced materials (Deerfield Beach, Fla.), 2010)
Direct growth of single-walled carbon nanotubes (SWNTs) on flat substrates by chemical vapor deposition (CVD) is very important for the application of SWNTs in nanodevices. In the growth process, catalysts play an important role in controlling the structure of SWNTs. Over the years, we have systematically studied the size-controlled synthesis of Fe-based nanoparticles and the CVD growth of SWNTs, especially the horizontally aligned SWNTs, catalyzed by these produced nanoparticles. Some new catalysts were also developed. Among them, Cu is shown to be a superior catalyst for growing SWNT arrays on both silicon and quartz substrates and Pb is a unique catalyst from which one can obtain SWNTs without any metallic contaminant. SWNTs prepared with both Cu and Pb are very suitable for building high-performance nanodevices. These studies are also very helpful for further understanding the growth mechanism of SWNTs